2015
DOI: 10.1186/s40623-015-0214-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural characteristics of the Bayonnaise Knoll caldera as revealed by a high-resolution seismic reflection survey

Abstract: The Bayonnaise Knoll caldera is a conical silicic caldera located on the eastern part of the back-arc rift zone of the Izu-Ogasawara arc. Many geological and geophysical surveys have shown that the Bayonnaise Knoll caldera contains hydrothermal sulfide deposits. The Japan Agency for Marine-Earth Science and Technology conducted high-resolution multi-channel seismic reflection surveys across the Bayonnaise Knoll caldera to ascertain details of the crustal structure, such as the configuration of faults around th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…1a), rather than being formed by simple upwelling fluid flow like the TAG mound on the Mid-Atlantic Ridge (e.g., Hannington et al 1998). A seismic study of the Bayonnaise caldera revealed fractures pervasively distributed inside of the caldera rim (Yamashita et al 2015). Yamashita et al (2015) postulated that these fractures induce fluid flow outside of the caldera rim.…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…1a), rather than being formed by simple upwelling fluid flow like the TAG mound on the Mid-Atlantic Ridge (e.g., Hannington et al 1998). A seismic study of the Bayonnaise caldera revealed fractures pervasively distributed inside of the caldera rim (Yamashita et al 2015). Yamashita et al (2015) postulated that these fractures induce fluid flow outside of the caldera rim.…”
Section: Modelingmentioning
confidence: 99%
“…A seismic study of the Bayonnaise caldera revealed fractures pervasively distributed inside of the caldera rim (Yamashita et al 2015). Yamashita et al (2015) postulated that these fractures induce fluid flow outside of the caldera rim. Further studies might elucidate the hydrological structure including this type of caldera-scale fluid flow that forms the Sunrise deposit.…”
Section: Modelingmentioning
confidence: 99%